EFISIENSI DENGAN KONVERSI SATUAN HARGA TINTA RP/GRAM MENJADI RP/SHEET PADA TINTA FLEKSO - Endang Yuniarti; Risya Kusna Putri (Politeknik Negeri Jakarta, 2019)
There agreement between ink companies and printing companies that is the ink company will supply printing ink according to the needs of the printing company and if there is excess ink, it will be requested. Ink returns according to company data reach 50 to 80%. The problem that arises is the problem of ink that will become junk, and the impact is inefficiency. The purpose of this study is to test the selling price unit of RP/KG ink to become RP/Sheet. The method used in this study is the calculation of BM area using Automatic Cad and is calculated using ink in gr/m2 units which is then used to be gr/sheet units and converted again to the unit price, which is Rp/sheet. The object of research is KKG instant noodles. This research resulted in the conversion of black and white price units used in this instant noodle product with units of Rp/gr indicating a more expensive price of Rp.49,806 per gram while with units of Rp/sheet of Rp17,34 per sheet. So by using units of Rp/sheet, give the ink company to estimate when sending ink so that it can be minimized from printing companies.